Comparative Analysis of Systems Thinking Application and Its Impact on Organizational Effectiveness in Sharia Banking - Sumairah, Sayeeda; Zainon, Edaiay (Inovasi Analisis Data, 2024)
Objective; Lack of ability in Sharia banking institutions to understand the systems of an organization, so that the organization is less effective. It delves into the impact of systems thinking on multiple dimensions of organizational performance such as decision-making, adaptability, strategic planning, employee performance etc.Methods; The study uses a cross-sectional survey design with primary data collected from a self-administered questionnaire distributed to employees across four Sharia banking institutions located in Indonesia, Malaysia, Pakistan and Yemen. The sample is reflected by lower and middle management levels and statistical analysis is carried out using multiple regression and confirmatory factor analysis (CFA).Results; The results show that systems thinking leads to better organizational effectiveness, evident in decision making, adaptability, and strategic planning. It also improves the performance of employees and develops the organizational culture. Furthermore, the relationship between systems thinking and organizational effectiveness was discovered to be moderated through organizational culture.Novelty; The objective of this research was to examine the novelty of systems thinking application particularly in the context of organizational effectiveness for Sharia banking institutions, identifying the cultural factors that affect systems thinking implementation.Research Implications; By providing practical recommendations for the incorporation of systems thinking within their organizational strategies, the research adds to the body of literature on Sharia banking institutions. That implies applying systems thinking leads to greater organizational success and a better outcome over the long run